"Potential Health Benefits of Lunasin: A Multifaceted Soy‐Derived Bioactive Peptide". Issue 3 (27th January 2015) - Lule, Vaibhao Kisanrao; Garg, Sheenam; Pophaly, Sarang Dilip; Hitesh; Tomar, Sudhir Kumar
Abstract Bioactive peptides are small protein fragments derived from enzymatic hydrolysis of food proteins, fermentation with proteolytic starter cultures, and gastrointestinal digestion. These peptides have positive impacts on a number of physiological functions in living beings. Lunasin, a soy‐derived bioactive peptide, is one of the most promising among them. Lunasin encoded within 2S albumin (GM2S‐1) gene, identified as a novel peptide extracted from soybean seed. It is composed of 43 amino acid residues with a molecular weight of 5.5 kDa. Extensive scientific studies have shown that lunasin possesses inherent antioxidative, anti‐inflammatory, anticancerous properties and could also play a vital role in regulating of cholesterol biosynthesis in the body. Its high bioavailability and heat stable nature allow its potential use as dietary supplement. The present review summarizes some of the potential health and therapeutic benefits of lunasin reported hitherto.